2020
DOI: 10.1111/and.13514
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of antioxidants in sperm parameters and production of reactive oxygen species levels during the freeze‐thaw process: A systematic review and meta‐analysis

Abstract: To investigate the impact of antioxidants in sperm parameters and reduction in reactive oxygen species production during the freeze‐thaw process. PubMed, Scopus, Web of Science, Embase and Cochrane central library were systematically searched. Of the 1583 articles, 23 studies were selected for data extraction. Our results show that antioxidants improved sperm progressive motility (standardised mean difference (SMD) = 1; 95% CI: 0.62, 1.38; p < .001) and viability (SMD = 1.20; 95% CI: 0.50, 1.91; p = .001) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…All measured nuclear alterations were significantly reduced by hypotaurine supplementation. The protective effects of hypotaurine on sperm nuclear integrity reported here confirmed our preliminary report [ 28 ] and are consistent with other reports that have shown that AO supplementation in freezing media protects sperm cells from DNA damage [ 2 , 5 , 23 ]. Our study demonstrates that the addition of AO to the selection and freezing media reduces both sperm nuclear vacuolization and alterations in chromatin packaging.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All measured nuclear alterations were significantly reduced by hypotaurine supplementation. The protective effects of hypotaurine on sperm nuclear integrity reported here confirmed our preliminary report [ 28 ] and are consistent with other reports that have shown that AO supplementation in freezing media protects sperm cells from DNA damage [ 2 , 5 , 23 ]. Our study demonstrates that the addition of AO to the selection and freezing media reduces both sperm nuclear vacuolization and alterations in chromatin packaging.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, publications showed that hypotaurine can scavenge the aggressive hydroxyl radical [ 36 , 51 ], but its ability to deal with H 2 O 2 (or/and H 2 O 2 -mediated damage) is not clearly established. It has recently been shown that different antioxidants, when combined, can have additive positive effects on spermatozoa (for recent reviews [ 2 , 5 , 22 , 23 ]). Other AO will be tested in combination with hypotaurine to measure potential synergistic and/or complementary action.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it may increase the number of leukocytes in semen and lead to hormone fluctuations (e.g., testosterone), causing disorders in the functioning of the male reproductive system and significantly reducing the ability to fertilize (3,(8)(9)(10). Thus, assessing the level of oxidative stress in the body should be included in male infertility diagnosis, and may be a useful tool in determining the ability to fertilize sperm (11).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants improved sperm viability, motility, and reduced sperm SDF [ 53 ]. The addition of GTE 0.1 mg/100 mL extender (T2 group, Table 3 ) revealed the lowest SDF, total, and types of ND1 mtDNA fragments mutation frequency.…”
Section: Discussionmentioning
confidence: 99%